2008
DOI: 10.1063/1.2838344
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxygen on the electronic configuration of Gd2O3∕Ge heterojunctions

Abstract: The band structure of the Gd2O3∕Ge heterojunction was investigated by x-ray photoelectron spectroscopy and was found to be very sensitive to variations of oxygen content in the oxide film. A 0.6eV decrease of the valence band offset (VBO) has been observed after in situ O2 postdeposition annealing (PDA). The VBO value obtained after PDA is 2.8eV in excellent agreement with data reported in the literature. The extra oxygen, supplied during PDA, is stably incorporated in the Gd2O3 matrix. Moreover, this extra ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…A strong oxygen 1s peak at 532.8 eV implied the oxygen existed in the O 2À oxidation state. 53 Clearly, on the basis of the composition and valence analysis, the as-prepared CGC 37 was composed of CuGeO 3 . To conrm the existence of graphene, the ne spectrum of C 1s from CGC 37 was examined (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A strong oxygen 1s peak at 532.8 eV implied the oxygen existed in the O 2À oxidation state. 53 Clearly, on the basis of the composition and valence analysis, the as-prepared CGC 37 was composed of CuGeO 3 . To conrm the existence of graphene, the ne spectrum of C 1s from CGC 37 was examined (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in the previous paragraph, our SIMS results showed that there were Zn-Si inter-diffusion at the ZnO/ SiO 2 interface of the as-grown samples and the interdiffusion would be significantly enhanced by thermal annealing. Studying the near-interfacial defects of oxide/ZnO interface, Wang et al 27 also showed that deep level defects were easily formed at the near-interfacial region, and it had the effect of enhancing the defect emission. In the present study, the 2.8 eV and the 3.0 eV peaks were only found in the E b ¼ 10 keV spectra, and were thus thought to be associated with defects located closer to the ZnO/SiO 2 interface.…”
Section: Resultsmentioning
confidence: 99%
“…Though indirectly, this result affirms the high sensitivity of the GeO 2 IL to the presence of a particular chemical agent. 17,18 Therefore, the effect of La may be associated with formation of the LaGeO x compound, 11 in which the formation of Ge sub-oxide of a certain kind is suppressed.…”
mentioning
confidence: 98%